Impact of Trade Openness, Human Capital Through Innovations on Economic Growth: Case of the Balkan Countries - Kurteš Siniša; Amidžić Srđan; Kurušić Drago (ECONOMICS, 2023)
The importance of trade openness and human capital for the economic growth of countries is the subject of many studies today. The role of innovations and the innovativeness of economies in modern economic development is extremely important. With greater accumulation of human capital, knowledge, skills and innovation are accumulated. All these variables are crucial for achieving higher economic growth. Special attention in the studies of relevant authors is directed towards researching this relationship on the example of small open economies, as well as developing countries. The purpose of this paper is to examine the relationship between trade openness and human capital as explanatory variables and GDP as a dependent variable in a sample of eight Balkan countries. The goal of the research is to quantify the relationship between two independent variables and GDP as a dependent variable. The period in which we observe this relationship covers the period from 2000 to 2019. Achieving the research objective is done on the basis of a panel model with fixed and random effects. The results of the panel research testify to the existence of a positive relationship between trade openness and human capital as independent variables and GDP as a dependent variable. Calculated coefficients with independent variables were obtained with a high level of statistical significance. The conclusion of the research implies that there is a positive impact of trade openness and human capital on GDP.